UTILIZATION OF DIAGNOSTICS OF NANDA INTERNATIONAL IN FRAIL ELDERLY - Lukšová, Hana; Vrublová, Yvetta (Profese Online, 2013)
There is no general definition of frailty in the elderly. Some authors describe it as a symptom, others as a complex syndrome, or as an accumulation of functional deficits in older adults. According to professional publications, frailty occurs in up to 25 percent of the elderly (Holmerová, 2007, p. 100). Developing of frailty in older adults may be subject to multimorbidity, undesired effects of medication, physical inactivity, malnutrition, loneliness or depression (Kalvach, 2008, p. 122). The aim of the article is to search for and analyse foreign scientific articles related to frailty in the elderly and to use gained knowledge in NANDA International diagnostics. To obtain the relevant data, electronic databases Pubmed, Medline, ProQuest, Springer and Google were used. Published articles concerning frailty in the elderly were found by a specific search strategy. Diagnostic elements were identified and nursing diagnoses were determined according to the diagnostic algorithm by NANDA International. Nursing diagnostics of NANDA International seems appropriate in providing nursing care to frail older adults.
Keywords: fragile; frailty; syndrome; elderly; nursing diagnostics; NANDA International